2016
DOI: 10.1213/ane.0000000000001349
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Efficacy of Inhibition Through Trafficking of γ-Aminobutyric Acid Type A Receptors

Abstract: Trafficking of anesthetic-sensitive receptors within the plasma membrane, or from one cellular component to another, occurs continuously. Changes in receptor trafficking have implications in altering anesthetic sensitivity. γ-aminobutyric acid type A receptors (GABAARs) are anion permeable ion channels and are the major class of receptor in the adult mammalian central nervous system that mediates inhibition. GABAergic signaling allows for precise synchronized firing of action potentials within brain circuits t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…NAS are accepted to play key roles as endogenous modulators of GABAergic inhibition, in part by acting as GABA A R PAMs (1,8). Recent studies have suggested that, in addition to their role as PAMs, NASs exert sustained metabotropic effects on GABAergic inhibition via an underlying mechanism that remains ill-defined (10,30). In addition to its role as a GABA A R PAM, ALLO has been shown to bind and activate mPRs, which have been proposed to be a novel family of GPCRs that are highly expressed in the brain (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…NAS are accepted to play key roles as endogenous modulators of GABAergic inhibition, in part by acting as GABA A R PAMs (1,8). Recent studies have suggested that, in addition to their role as PAMs, NASs exert sustained metabotropic effects on GABAergic inhibition via an underlying mechanism that remains ill-defined (10,30). In addition to its role as a GABA A R PAM, ALLO has been shown to bind and activate mPRs, which have been proposed to be a novel family of GPCRs that are highly expressed in the brain (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The γ2 subunit is important for efficient trafficking of GABA A Rs to the cell membrane (Nakamura et al, 2015 ; Vien et al, 2016 ) and for GABA A R clustering at synapses (Essrich et al, 1998 ; Alldred et al, 2005 ). Hereditary epilepsy mutations to γ2 impair channel function by various means including ER retention of misfolded subunits, mutant subunit aggregation, dominant negative suppression of partner subunits, impaired channel gating and aberrant synaptic targeting (Kang and Macdonald, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main task of these vesicles is the transport of specific membrane proteins, synthesized in the endoplasmic reticulum (ER), to critical sites of the cell surface. Transported proteins include subunits and/or whole proteins of receptors, channels, pumps, transporters, and others (Flowerdew and Burgoyne, 2009; Dumoulin et al, 2011; Luscher et al, 2011; Tanaka and Hirano, 2012; Jurado et al, 2013; Martinez-Mamol et al, 2013; Hussain and Davanger, 2015; Gu et al, 2016; Gu and Huganir, 2016; Hussain et al, 2016; Langlhofer and Villmann, 2016; Meneses et al, 2016; Vien et al, 2016; Jaldin-Fincati et al, 2017; Klemens et al, 2017; Pick et al, 2017; Roth et al, 2017; Wu et al, 2017).…”
Section: General Organization Of the Reviewmentioning
confidence: 99%
“…Also in this case, the SNARE complexes that govern the exocytosis of resting and stimulated vesicles are different (Gu and Huganir, 2016; Hussain et al, 2016). The vesicles of subunits of other receptors, the inhibitory GABA A and glycine receptors, are also involved in non-secretory exocytosis, analogous to those of glutamate receptors (Dumoulin et al, 2011; Luscher et al, 2011; Langlhofer and Villmann, 2016; Vien et al, 2016). In neurons, therefore, the specific roles of the receptors and their subunits strongly suggest that the exocytosis of many non-secretory vesicles, distinct in terms of specificity, participates in distinct physiological functions.…”
Section: Generation and Initial Traffic Of The First Group Of Non-secmentioning
confidence: 99%
See 1 more Smart Citation